HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PD. RABINDO TAMA SERANG BANTEN (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
The development of the times is certainly influenced by the increase in the human population so that the need for clothing, food and shelter increases. The need for boards is especially important because it is in line with the increasing demand for building materials or materials.This study aims to examine the effect of price and service quality with purchasing decisions on PD. Rabindo Tama Serang Banten. By using a descriptive analytical approach which is a quantitative research. Total population of all who have become consumers of PD. Rabindo Tama and took 66 research samples. The main problems and objectives formulated in the Purchasing Decision (Y) research through Price (X1) and Service Quality (X2) at PD. Rabindo Tama Serang Banten, then the method of this research is descriptive analytical method that is looking at the causal relationship. Based on the research analysis, the coefficient of determination (R2) = 72.4%. The results of the partial test are X1 variables of 6.755 and X2 of 4.266, which is greater than ttable of 1.99773 and the value of sig. < 0.05. The results of the study simultaneously obtained the results of Fcount = 82.435 > Ftable = 3.14. Based on the results of the study, it can be concluded that the effect of the variable price and service quality partially and simultaneously on purchasing decisions has a significant and positive effect. Keywords: Price, Service Quality, Purchase Decision